Statement of Peer Review—The 2024 10th International Conference on Advanced Engineering and Technology - Jongwan Hu; Dongkeon Kim; Mosbeh Kaloop (Materials Proceedings)
In submitting conference proceedings to Materials Proceedings, the Volume Editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review, administered by the Volume Editors [...]